Effect of Fulani Herdsmen Grazing Activities on Food Crop Production among Farm Youth in Nigeria - Kolawole Adelekan Adeloye; Dixon Olutade Torimiro; Kazeem Babatunde Oladejo (Talenta Publisher, 2023)
This study investigated the effect of herdsmen grazing activities on food crop production among farm youth in Nigeria. Data were collected from 120 farm youth through a structured interview schedule with a multi-stage selection process. Data analysis was done using appropriate statistics. The results reveal mean age and experience in farming of the youth were 29.03± 1.9 years and 11.11 ±7.22 years, respectively. Many (69.2%) of them were male with at least 77.5% having primary school education, and 60.88% had experienced the occurrence of Fulani herdsmen grazing activities in the past three years. In addition, 98.3 percent experienced a high effect of Fulani herdsmen grazing activities on their food crop production. Verbal warning (mean = 2.96) ranked highest among coping strategies adopted by farm youth, followed by local security (mean = 1.94) among others. At p<0.01, the perception of the grazing activities (r = 0.595), experience in farming (r = 0.411), and coping strategies (r = 0.446) had a substantial association with the effect of the Fulani herdsmen grazing activities on food crop production. The study then concluded that the Fulani herdsmen grazing activities had a high effect on the food crop production of the farm youth.